Molecular Characterization and Pathogenicity Analysis of Porcine Rotavirus A - Yaning Lv; Ze Tong; Jiaqi Liu; Zhaoran Zhang; Chenchen Wang; Yan Zeng; Pingxuan Liu; Xin Zong; Guosheng Chen; Huanchun Chen; Chen Tan (Viruses, 2024)
Porcine rotavirus A (RVA) is one of the major etiological agents of diarrhea in piglets and constitutes a significant threat to the swine industry. A molecular epidemiological investigation was conducted on 2422 diarrhea samples from Chinese pig farms to enhance our understanding of the molecular epidemiology and evolutionary diversity of RVA. The findings revealed an average RVA positivity rate of 42% (943/2422), and the study included data from 26 provinces, primarily in the eastern, southern and southwestern regions. Genetic evolutionary analysis revealed that G9 was the predominant genotype among the G-type genotypes, accounting for 25.32% of the total. The VP4 genotypes were P[7] (36.49%) and P[23] (36.49%). The predominant genotypic combinations of RVA were G9P[23] and G9P[7]. Eleven RVA strains were obtained via MA104 cell isolation. A rat model was established to assess the pathogenicity of these strains, with three strains exhibiting high pathogenicity in the model. Specifically, the RVA Porcine CHN HUBEI 2022 (Q-1), RVA Porcine CHN SHANXI 2022 (3.14-E), and RVA Porcine CHN HUBEI 2022 (5.11-U) strains were shown to cause diarrhea in the rats and damage the intestinal villi during the proliferation phase of the infection, leading to characteristic lesions in the small intestine. These data indicate that continuous monitoring of RVA can provide essential data for the prevention and control of this virus.